Pick Simply the Best: Sustainable Development is About Radical Analysis and Selective Synthesis, not About Old Wine in New Bottles. (17th April 2013) - Spangenberg, Joachim H.; Springett, Delyse
ABSTRACT For sustainable development, accepting limits is one of the two guiding principles identified by the Brundtland Commission (the other one being satisfying human needs). This can be achieved by slimming an economy, limiting the total amount of resources it consumes. While stabilizing resource consumption at the present levels seems to be a minor challenge, dematerializing the economy sufficiently to allow for equitable consumption of all the Earth's citizens, while reducing environmental pressures significantly, is a major challenge. A means to implement this could be a cap to resource use, combined with access allocation mechanisms not specified in this paper. With a depreciation of the input volumes, the result would be a change in the economic dynamics, and in the very functioning of the respective society and economy. Distribution issues would gain prominence, social security would be a key concern, private property would need to be complemented by a more efficient method of product use such as product sharing, and corporate ownership structures might change significantly. It has been questioned whether such a resource‐limited economy could still be a market‐driven one. By identifying some of the objections as based not on reality but on methodological flaws of economic theory, it can be shown that a market economy can survive such transformations, albeit with the need to complement it by other allocation mechanisms. The resulting society might still be called a capitalist one; it would significantly differ from current capitalism, but not resemble past socialist economies. Rather than categorizing it as one or the other, or than deriving new '‐isms', the discussion should focus on the practical means to pursue the sustainable transformation of our societies and economies. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.